1998
DOI: 10.1017/s0007485300025748
|View full text |Cite
|
Sign up to set email alerts
|

Selection for and against resistance to insecticides in the absence of insecticide: a case study of malathion resistance in the saw-toothed grain beetle,Oryzaephilus surinamensis(Coleoptera: Silvanidae)

Abstract: In the absence of insecticide there may be intense selection against alleles conferring insecticide resistance, so that these alleles will decline in frequency. On the other hand, selection will act to favour alleles at modifier loci which cause resistance alleles to become coadapted and increase in fitness even in the absence of insecticide. The relative effectiveness of these two processes is of practical importance and theoretical interest. The fate of polymorphism for malathion resistance was studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Restricted relative Þtness estimates in the absence of selection pressure were 0.79 for the resistant homozygote and 0.89 for the heterozygote and were statistically different from zero and unity at the 5% signiÞcance level. These estimates were similar to relative Þtness estimates reported for the saw-toothed grain beetle, Oryzaephilu surinamensis (L.) (Coleoptera: Silvanidae), in the absence of malathion selection pressure (Muggleton 1986, Mason 1998. Muggleton (1986) reported relative Þtness estimates for resistant homozygotes and heterozygotes of 0.82 for both genotypes, assuming resistance was conferred by one dominant allele at one locus.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Restricted relative Þtness estimates in the absence of selection pressure were 0.79 for the resistant homozygote and 0.89 for the heterozygote and were statistically different from zero and unity at the 5% signiÞcance level. These estimates were similar to relative Þtness estimates reported for the saw-toothed grain beetle, Oryzaephilu surinamensis (L.) (Coleoptera: Silvanidae), in the absence of malathion selection pressure (Muggleton 1986, Mason 1998. Muggleton (1986) reported relative Þtness estimates for resistant homozygotes and heterozygotes of 0.82 for both genotypes, assuming resistance was conferred by one dominant allele at one locus.…”
Section: Resultssupporting
confidence: 78%
“…Muggleton (1986) reported relative Þtness estimates for resistant homozygotes and heterozygotes of 0.82 for both genotypes, assuming resistance was conferred by one dominant allele at one locus. Mason (1998) reported relative Þtness estimates of 0.92, 0.83, and 0.68 for both genotypes in three experiments under the same assumption. Finally, environmental effects on Þtness in May and June were statistically different from unity at the 5% signiÞcance level in the unrestricted and restricted models, suggesting that tobacco budworms may have been less able to survive the vial test bioassay at the beginning relative to the end of the growing season.…”
Section: Resultsmentioning
confidence: 97%
“…Based on antagonistic selective pressures principle that insecticide selection favors resistant individuals and resistance Þtness cost disadvantages them in the absence of insecticides and in accordance with Georghiou et al (1983), Mallet (1989), Bonning and Hemingway (1991), Hemingway et al (1992), Rodriguez et al (1993), Tabashnik (1994), Guillemaud et al (1998), Mason (1998), and Lenormand and Raymond (1998), several strategies can be used in resistance management: 1) Temporal (window strategy) or spatial (mosaic strategy) rotation involves alternation of insecticide selection and no-selection periods. Nevertheless, insecticide rotation efÞciency can encounter the problem of modiÞer gene selection that reduces resistance Þtness costs (Mason 1998).…”
Section: Cypermethrin Toxicity To H Armigera Strains Collected In mentioning
confidence: 68%
“…However, despite the extensive literature on the subject, there are relatively few empirical studies that confirm that investment in such adaptations exacts a cost (Minkoff and Wilson, 1992;Carriere et al, 1994Carriere et al, , 1995Yamamoto et al, 1995;Chevillon et al, 1997;Alyokhin and Ferro, 1999;Boivin et al, 2001). Some authors have failed to reveal any detrimental effects of insecticide resistance (Follett et al, 1993;Tang et al, 1997Tang et al, , 1999Baker et al, 1998) and some have shown such organisms to be even more successful than their susceptible counterparts in the absence of insecticides (Omer et al, 1992;Bloch and Wool, 1994;White and Bell, 1995;Mason, 1998;Haubruge and Arnaud, 2001). In other studies, some measures of fitness have been negatively affected, others positively (Brewer and Trumble, 1991) and different strains of insect, exhibiting resistance to the same compound, can show opposite associations (Chevillon et al, 1997;Hollingsworth et al, 1997;Oppert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%